2014
DOI: 10.1016/j.neuropharm.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid amide hydrolase inhibitor PF-3845 promotes neuronal survival, attenuates inflammation and improves functional recovery in mice with traumatic brain injury

Abstract: Traumatic brain injury (TBI) is the leading cause of death in young adults in the United States, but there is still no effective agent for treatment. N-arachidonoylethanolamine (anandamide, AEA) is a major endocannabinoid in the brain. Its increase after brain injury is believed to be protective. However, the compensatory role of AEA is transient due to its rapid hydrolysis by the fatty acid amide hydrolase (FAAH). Thus, inhibition of FAAH can boost the endogenous levels of AEA and prolong its protective effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 58 publications
(89 reference statements)
2
92
0
Order By: Relevance
“…By contrast, in the neonatal rat brain, the exposure to concussive head trauma induced a moderate increase in the levels of anandamide and other N-acylethanolamines, but not of 2-AG and other 2-monoacylglycerols [43,44]. Further studies demonstrated that these elevations are endogenous responses addressed to limit brain damage, as the inhibition of 2-AG and anandamide hydrolysis reduced brain damage and improved functional deficits in parallel to a reduction of proinflammatory responses in the mouse brain after TBI [45,46]. Similar elevations of anandamide, 2-AG, and Nacylethanolamines have been detected in experimental cerebral ischemia [47][48][49][50].…”
Section: Cannabinoids and Acute Brain Damage: Stroke And Brain Traumamentioning
confidence: 93%
“…By contrast, in the neonatal rat brain, the exposure to concussive head trauma induced a moderate increase in the levels of anandamide and other N-acylethanolamines, but not of 2-AG and other 2-monoacylglycerols [43,44]. Further studies demonstrated that these elevations are endogenous responses addressed to limit brain damage, as the inhibition of 2-AG and anandamide hydrolysis reduced brain damage and improved functional deficits in parallel to a reduction of proinflammatory responses in the mouse brain after TBI [45,46]. Similar elevations of anandamide, 2-AG, and Nacylethanolamines have been detected in experimental cerebral ischemia [47][48][49][50].…”
Section: Cannabinoids and Acute Brain Damage: Stroke And Brain Traumamentioning
confidence: 93%
“…AEA exerts an antiinflammatory effect on microglia by increasing the expression of CD200R, which is important for the inhibitory neuronal control of microglia [9] and by facilitating the expression of anti-inflammatory cytokines [10] . Treatment with FAAH inhibitors protected neurons against NMDA-induced excitotoxicity in organotypic hippocampal slice cultures [11] and also in vivo in mice with traumatic brain injury [12] . The decreased expression of pro-inflammatory [13,14] and increased expression of antiinflammatory mediators in activated microglia suggest that AEA induces a shift of microglial phenotype from M1 to M2 [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with FAAH inhibitors protected neurons against NMDA-induced excitotoxicity in organotypic hippocampal slice cultures [11] and also in vivo in mice with traumatic brain injury [12] . The decreased expression of pro-inflammatory [13,14] and increased expression of antiinflammatory mediators in activated microglia suggest that AEA induces a shift of microglial phenotype from M1 to M2 [12] . It was suggested that the neuroprotective effect of AEA is mediated by CB1 and CB2 receptors [15] , whereas both cannabinoid receptor dependent [10] and independent [16] effects of AEA on microglial activity were reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, AEA has been reported to inhibit inflammatory responses in experimental hepatitis (Hegde et al, 2008), inflammatory bowel disease (Di Sabatino et al, 2011), LPS-induced pulmonary inflammation (Berdyshev et al, 1998), nephropathy (Mukhopadhyay et al, 2010a, b), and multiple sclerosis (Mestre et al, 2005). Additional studies demonstrate that elevation of AEA levels by genetic knockout or chemical inhibition of the AEA degradative enzyme fatty acid amide hydrolase ameliorates traumatic brain injury-induced neuronal inflammation and cystitis-associated pain sensation (Tchantchou et al, 2014;Wang et al, 2015). However, the mechanism by which endocannabinoids, in particular AEA, impart their anti-inflammatory effect remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories have reported inhibitory effects on inflammation and associated diseases and pathologic phenomena by elevating endogenous AEA levels through different approaches, including fatty acid amide hydrolase gene KO (Naidu et al, 2010;Kinsey et al, 2011;Wang et al, 2015), fatty acid amide hydrolase inhibitors (Kinsey et al, 2011;Schuelert et al, 2011;Booker et al, 2012;Caprioli et al, 2012;Kerr et al, 2012;Murphy et al, 2012;Sasso et al, 2012;Krustev et al, 2014;Sałaga et al, 2014;Tchantchou et al, 2014), and AEA reuptake inhibitors (Mestre et al, 2005;D'Argenio et al, 2006). Further studies are needed to address whether such approaches are also protective in glomerular injury associated with hHcys.…”
Section: Discussionmentioning
confidence: 99%